Acute Neurological Illness in a Kidney Transplant Recipient Following Infection With Enterovirus‐D68: An Emerging Infection?. Issue 12 (30th July 2015) - Wali, R. K.; Lee, A. H.; Kam, J. C.; Jonsson, J.; Thatcher, A.; Poretz, D.; Ambardar, S.; Piper, J.; Lynch, C.; Kulkarni, S.; Cochran, J.; Djurkovic, S.
Abstract : We report the first case of enterovirus‐D68 infection in an adult living‐donor kidney transplant recipient who developed rapidly progressive bulbar weakness and acute flaccid limb paralysis following an upper respiratory infection. We present a 45‐year‐old gentleman who underwent pre‐emptive living‐donor kidney transplantation for IgA nephropathy. Eight weeks following transplantation, he developed an acute respiratory illness from enterovirus/rhinovirus that was detectable in nasopharyngeal (NP) swabs. Within 24 h of onset of respiratory symptoms, the patient developed binocular diplopia which rapidly progressed to multiple cranial nerve dysfunctions (acute bulbar syndrome) over the next 24 h. Within the next 48 h, asymmetric flaccid paralysis of the left arm and urinary retention developed. While his neurological symptoms were evolving, the Centers for Disease Control reported that the enterovirus strain from the NP swabs was, in fact, Enterovirus‐D68 (EV‐D68). Magnetic resonance imaging of the brain demonstrated unique gray matter and anterior horn cell changes in the midbrain and spinal cord, respectively. Constellation of these neurological symptoms and signs was suggestive for postinfectious encephalomyelitis (acute disseminated encephalomyelitis [ADEM]) from EV‐D68. Treatment based on the principles of ADEM included intensive physical therapy and other supportive measures, which resulted in a steady albeit slow improvement in his left arm and bulbar weakness, while maintaining stable allograft function. Abstract : The authors report a case of enterovirus‐D68 respiratory infection in a kidney transplant recipient who developed acute neurological symptoms of bulbar and flaccid limb paralysis, with steady but slow recovery with intensive treatment.